Universal and Selective Interventions to Prevent Poor Mental Health Outcomes in Young People: Systematic Review and Meta-analysis. Issue 3 (May 2021) - Salazar de Pablo, Gonzalo; De Micheli, Andrea; Solmi, Marco; Oliver, Dominic; Catalan, Ana; Verdino, Valeria; Di Maggio, Lucia; Bonoldi, Ilaria; Radua, Joaquim; Baccaredda Boy, Ottone; Provenzani, Umberto; Ruzzi, Francesca; et al.
Abstract : Supplemental digital content is available in the text. Abstract: Background: Much is not known about the efficacy of interventions to prevent poor mental health outcomes in young people by targeting either the general population (universal prevention) or asymptomatic individuals with high risk of developing a mental disorder (selective prevention). Methods: We conducted a PRISMA/MOOSE-compliant systematic review and meta-analysis of Web of Science to identify studies comparing post-test efficacy (effect size [ES]; Hedges' g) of universal or selective interventions for poor mental health outcomes versus control groups, in samples with mean age <35 years (PROSPERO: CRD42018102143). Measurements included random-effects models, I 2 statistics, publication bias, meta-regression, sensitivity analyses, quality assessments, number needed to treat, and population impact number. Results: 295 articles (447, 206 individuals; mean age = 15.4) appraising 17 poor mental health outcomes were included. Compared to control conditions, universal and selective interventions improved (in descending magnitude order) interpersonal violence, general psychological distress, alcohol use, anxiety features, affective symptoms, other emotional and behavioral problems, consequences of alcohol use, posttraumatic stress disorder features, conduct problems, tobacco use, externalizing behaviors, attention-deficit/hyperactivity disorder features, and cannabis use, but not eating-related problems, impaired functioning, internalizing behavior, or sleep-related problems. Psychoeducation had the highest effect size for ADHD features, affective symptoms, and interpersonal violence. Psychotherapy had the highest effect size for anxiety features. Conclusion: Universal and selective preventive interventions for young individuals are feasible and can improve poor mental health outcomes.